Color centers in K–Na–Cl crystals induced by pulsed intense relativistic electron beam at 77 K. (1st February 2022) - Namioka, Yoji; Kurosaki, Taisei; Kikuchi, Takashi; Dung, Do Thi Mai; Nakayama, Tadachika; Suematsu, Hisayuki; Thorogood, Gordon J.
Abstract: In order to reproduce the irradiation environment of Europa, NaCl-0-2mol%KCl crystals were grown and irradiated with pulsed intense relativistic electron beams at RT and 77 K in the optical absorbance spectra. The peak wavelength of the F-center was shortened by decreasing the measurement temperature and the KCl content. This phenomenon can be explained by the changes of the lattice constant and utilized to determine temperature and KCl content in the sea of Europa.